Evaluation of Trans Metro Deli Bus Performance in Corridor 2 in an Effort to Improve the Quality of Public Services - Silalahi, Putri Permata; Hasibuan, Gina Cynthia Raphita; Anas, Ridwan (Universitas Ibn Khaldun Bogor, 2025)
TransMetro Deli Urban Transport is a bus-based transportation system in Medan City that started operating on 22 November 2020, with a Bus Rapid Transit (BRT) transportation system. TransMetro Deli buses provide 5 corridors around the area in Medan City. For Route K2M Terminal Amplas - Bank Indonesia - Terminal Amplas has a fleet of 10 main units and 2 backup units and passes 36 stops. This research begins with collecting data in the field directly and then analyzed including load factor, Headway, stopping time, and travel time on Weekdays and Weekends on the K2M route. Based on the analysis results obtained for Load Factor in Weekdays for Morning, Afternoon, and Evening are 14%, 8%, and 20%, while for Weekend are 12%, 15%, and 20%. For Headway in Weekdays in the Morning, Afternoon, and Evening are 10 minutes 16 seconds, 10 minutes 27 seconds, and 11 minutes 31 seconds, while in Weekend are 9 minutes 47 seconds, 9 minutes 40 seconds, and 10 minutes 2 seconds. For Downtime on Weekdays in the Morning, Afternoon, and Evening are 9 seconds, 9 seconds, and 10 seconds, while for Weekend are 7 seconds, 7 seconds, and 8 seconds. For Travel Time in Weekdays in the Morning, Afternoon, and Evening are 1 hour 13 minutes, 1 hour 16 minutes, and 1 hour 18 minutes, while in Weekend are 1 hour 3 minutes, 1 hour 14 minutes, and 1 hour 13 minutes.